INTERNALISASI NILAI-NILAI POLITIK KEBANGSAAN DAN PENANAMAN IDEOLOGI - UT, Abdullah; Abdullah, Abdullah; Akhyar, Taufik; Sari, Mayang (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research is about the internalization of national political values and the cultivation of ideology towards the regeneration process carried out by the Indonesian Democratic Party of Struggle of OKI Regency to its cadres.This research aims to find out how the internalization of national political values and the cultivation of ideology towards the regeneration process of the Indonesian Democratic Party of Struggle of OKI Regency. The research data was collected through direct interviews with informants, namely PDIP members.This data is processed using data condensation, data presentation, drawing conclusions.The theory used in the research is Herman Giescake's theory in the theory there are 4 definitions of political education including; 1.Bildungwissen 2.Orientierrungwissen 3.Verhaltungsweisen 4.Aktionwissen. The method used is qualitative descriptive .The results of this study show that the cultivation of political values and ideology carried out by the PDIP of OKI Regency is political education by using themes regarding national political values and party ideology, Gotong Royong Movement for Party Independence, and Internal Consolidation and Cadre Debriefing which utilizes the role of presenters to convey national political values and ideology. This can affect the success and failure of the regeneration process, and the Commitment of the PDIP Party Management, the existence of commitment will have an influence on the implementation of the internalization of values and the cultivation of ideology in the form of a mutual agreement between party administrators in carrying out one of the party's functions.